Pemberdayaan Masyarakat melalui Pelatihan Eco Enzyme Berbasis Limbah Organik Rumah Tangga pada Program KKN 28 UIN Sunan Ampel Surabaya di Desa Bangunrejo Kidul, Kabupaten Ngawi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Household organic waste management remains a significant environmental challenge in Bangunrejo Kidul Village, Kedunggalar District, Ngawi Regency, where open burning is still widely practiced due to limited knowledge of sustainable waste management. This community service program aimed to enhance community awareness, knowledge, and practical skills in utilizing household organic waste through the production of eco-enzyme as an environmentally friendly and multifunctional product. The program employed a Participatory Action Research (PAR) approach involving observation, planning, counseling, demonstrations, hands-on practice, mentoring, and evaluation. The activities were conducted by the 28th Community Service Program (KKN) students of UIN Sunan Ampel Surabaya in collaboration with local residents, village officials, and community health volunteers across several hamlets. The findings indicated that participants gained a better understanding of household organic waste management, successfully learned the eco-enzyme production process using the 1:3:10 ratio of molasses, organic waste, and water, and demonstrated the ability to independently apply the production techniques. The combination of educational sessions, demonstrations, and direct practice encouraged active community participation and strengthened environmental awareness. Furthermore, the program introduced eco-enzyme as a sustainable alternative for reducing organic waste burning while providing practical benefits as an organic fertilizer, natural pesticide, livestock sanitation agent, and multipurpose cleaning solution. These outcomes suggest that participatory community empowerment can promote sustainable household waste management and support environmentally responsible agricultural and livestock practices in rural communities